Freshmen mental health diagnostics in higher education institutions under martial law - Kots, Mykhailo; Babii, Mykola; Duchyminska, Tamara (Psychological Prospects Journal, 2024)
Purpose. Empirical study of mental health of first-year students of higher education institutions under martial law conditions. Methods. The research program was developed to achieve the goal, which included four diagnostic methods: the questionnaire ‘Self-assessment of states of anxiety, frustration, aggressiveness and rigidity” (adapted version of H. Eysenck method), the “Resistance to stress” test, “Questionnaire for measuring the locus of health control” (K. Wallston, B.S. Wallston, & R. Devellis) (adaptation by L. Karamushka, K. Tereshchenko, O. Kredentser), “Positive mental health scale (pmh-scale)” (J. Lukat, J. Margraf, R. Lutz, W.M. Van Der Veld, & E.S. Becker) (adaptation by L. Karamushka, O. Kredentser, K. Tereshchenko). Results. According to the study results, it was found that the majority of young people of early adolescence take an ambivalent position in choosing a strategy for assessing their own emotional states and follow the same tactics in choosing options for supporting and preserving mental health under the martial law conditions. They are rigid in the options for its change, since such actions are tested for effectiveness, and therefore have practical value. Such a behavioral strategy helps to keep the degree of anxiety, stress resistance and aggression at average levels, to maintain an internal emotional balance and to feel healthy and happy. Another part of respondents who participate in our empirical study gravitate towards extreme options for controlling their own physical condition. Young people with external locus of control rely more on the help of external circumstances, which will be useful for the return of internal harmony. Students with internal locus of control rely solely on themselves when choosing an option for maintaining mental health. It is difficult to determine which of these positions is more rational, it is important that it is as effective as possible in maintaining mental health. That actualizes the study of the outlined problems. Conclusions. The conducted theoretical and empirical research confirms the effectiveness of the proposed diagnostic program for mental health of first-year students of higher education institutions under the martial law conditions. We see the prospect of further study in the development of empirical research programs of other components of mental health and involvement of persons of various ages into the research.